An In Vitro Comparison of Costimulatory Domains in Chimeric Antigen Receptor T Cell for Breast Cancer Treatment - Nattarika Khuisangeam; Sirirut Jewmoung; Rattapoom Thaiwong; Suparat Tudsamran; Nattiya Hirankarn; Koramit Suppipat; Supannikar Tawinwung (Journal of Immunology Research)
Adoptive cellular therapy with chimeric antigen receptor (CAR) T cells has emerged as a potential novel treatment for various cancers. In this study, we have generated CAR T cells targeting mucin-1 (MUC1), which is an aberrantly glycosylated antigen overexpressed on breast cancer cells. Two different signaling domains, including CD28 and 41BB, were incorporated and directly compared the superiority of different costimulatory signals. Two different CAR MUC1 constructs were transduced into primary T cells and evaluated their characteristics and antitumor activities against MUC1+ cancer cells. CAR MUC1 T cells showed high transduction efficiency and antigen specificity toward MUC1+ cancer cell lines and primary breast cancer cells. When coculturing with target cells, the transduced cells exhibited potent antitumor activity in vitro and secrete proinflammatory cytokines. Upon antigen stimulation, incorporation of the 41BB signaling domain was able to improve T cell proliferation and reduce surface PD1 expression and the upregulation of suppressive cytokines, when compared with CAR MUC1 containing the CD28 domain. Our findings show that CAR T cell targeting MUC1 can be effective against MUC1+ breast cancer cell and support the further development of CAR MUC1 T cells containing 41BB signaling in preclinical and clinical studies of breast cancer treatment.